Dissemination of climate-smart agriculture practices in the Upper West Region of Ghana: insights from local stakeholders and institutions - Stephen Uwumbordo Nachibi; Abdul Wahid Arimiyaw; Eugene Muobom Ganee; Anthony Kwame Morgan (International Journal of Agricultural Sustainability)
Limited empirical evidence exist on local-level institutions’ innovations and experiences in facilitating climate-smart agriculture (CSA) adoption. Qualitative interviews with farmers and local institutions supporting agriculture in Nandom, Ghana, were conducted. We found that local-level institutions employed (1) farmer-field schools (FFS) for capacity building to provide relevant knowledge for managing CSA practices; and (2) credit extension packages to reduce financial barriers to accessing inputs and technologies for CSA. We also found that sociocultural, financial, logistical, and technological constraints are the most important barriers hampering local-level institutions` ability to effectively facilitate CSA adoption. Furthermore, we observed that to encourage the uptake of CSA practices, particularly among vulnerable groups such as women, social power dynamics surrounding resource access and utilization must be addressed. For practice, the findings (1) serve as a case for learning different innovations that can be adapted in different contexts; and (2) give insights on how to overcome social barriers to CSA adoption and facilitation. We recommend that governmental institutions such as the Ministry of Food and Agriculture allocate resources and design policies that builds the of implementers. Training institutions must tailor contents to the needs and assimilation levels of target communities. Additionally, development partners should establish long-term funding mechanisms beyond grant cycles to provide sustainable financial support for CSA upscale.